Limited engagement in, yet clear preferences for advance care planning in young-onset dementia: An exploratory interview-study with family caregivers. (October 2019) - Van Rickstal, Romy; De Vleminck, Aline; Aldridge, Melissa D; Morrison, Sean R; Koopmans, Raymond T; van der Steen, Jenny T; Engelborghs, Sebastiaan; Van den Block, Lieve
Background: The significance of advance care planning in dementia is widely acknowledged. Despite the suggestion that younger people with dementia and their family might have distinct needs and preferences in this area, studies on advance care planning in young-onset dementia are absent. Aim: We aim to explore (1) whether family caregivers had already engaged in advance care planning with patients and/ or professionals and the accompanying reasons and (2) family caregivers' preferences for how to ideally engage in the process with patients, family and professionals. Design: A qualitative study was conducted: we analysed semi-structured interviews ( n  = 15) through the method of constant comparative analysis. Setting/participants: We included Flemish family caregivers of persons with young-onset dementia. Results: Plans for the future typically concerned non-medical affairs. Participants' limited engagement in advance care planning was clarified through several reasons: not considering it useful, hindering patient behaviour, adopting a day-to-day attitude, caregivers emotionally protecting themselves and uncertainty about patients' cognitive competence. However, endorsement for advance care planning showed from respondents' preferences that it should be initiated timely, by a third party, and emphasize patients' remaining capacities. Finally, the need for information and high-quality care emerged. Conclusion: A gap of knowledge, of information and in care intertwiningly hinder advance care planning. In young-onset dementia, engaging in advance care planning is not an option equally accessible as not doing so. Policy makers, institutions and professionals could reflect on their responsibility in providing these patients and caregivers an actual choice to engage in advance care planning or not.